Acute conjunctivitis caused by an atypical chlamydial strain: Chlamydia IOL 207. Issue 6 (June 1984) - Forsey, T.; Darougar, S.
Abstract : A case of acute conjunctivitis in man caused by Chlamydia IOL 207 is described. Chlamydiae were isolated from the eye, and rising titres of type-specific antibodies to C. IOL 207, in serum and tears demonstrated an aetiological role for this agent. C. IOL 207 is an atypical chlamydial strain which serological studies suggest is widespread in some communities.